Design of a Double Cavity Nanotube Tunnel Field-Effect Transistor-based Biosenser. (1st August 2022) - Gedam, Anju; Acharya, Bibhudendra; Mishra, Guru Prasad
Abstract : The manuscript focused on the concept of junction-less tunnel transistor to suggest and simulate the dielectric modulated double cavity nanotube TFET as a biosensor. The proposed biosensor worked as a label-free detector about dielectric constant (K) and charge density ( ρ ). In this, for neutral biomolecules (streptavidin and 3-aminopropyl-triethoxysilane (APTES)) and charged biomolecule (deoxyribonucleic acid (DNA)) are used for detection by the proposed sensor. The inner and outer cavities of the nanotube biosensor provide a large area for the stabilization of biomolecules and use the benefits of material solubility. The sensing capability of the proposed device investigates various DC performance parameters for the different dielectric biomolecules and charge densities. Further, the effect of substitution of SiO2 gate insulating layer by HfO2 also studies the sensing capability of the proposed biosensor. Moreover, a relative study of the biosensor for the presence and absence of inner and outer nanogap cavities performs in terms of different DC components to analyze the sensitivity variation.